Tradition: where MacIntyre meets Hayek to Ground Ethical Governance - Maria-Clara Figueiredo-Dalla-Costa-Ames; Ana-Luize-Correa Bertoncini; Elize Jacinto; Marcello-Beckert Zappellini (Revista Empresa y Humanismo, 2024)
This article explores the concept of tradition as the broader ethical dimension in governance networks. We comprehensively address the notions of traditions from the work of the philosopher Alasdair MacIntyre and the economist Friedrich Hayek. Unlike the standard view, MacIntyre and Hayek offer some common understanding regarding the role of tradition in society. Both authors find support in the natural law tradition through different paths. Based on a review of their works, we point to preliminary directions for considering the dynamic of traditions in governance networks. Traditions involve spontaneous and organized means, the sharing of accumulated wisdom, and the ground to define the common good. Network governance represents a context where different traditions meet.